Pengaruh Variasi Aktivator dan Doping terhadap Nilai Daya Hantar Listrik dan Karakterisasi Karbon dari Bambu (Effect of Activator and Doping Variation on The Electrical Conductivity and Carbon Characteristics of Bamboo) - Rizka Karima; Nurmilatina Nurmilatina (Jurnal Riset Industri Hasil Hutan, 2018)
An added value of bamboo charcoal that is commonly used as an energy source could be increased by the addition of activator and metal doping. The objective of this research was to analyze the effect of the addition of activator and doping to the electrical conductivity and carbon characteristics for a raw material of bio-battery. Bamboo plantsused in this experiment were buluh, haur, and betung. Bamboo was carbonized inthe temperature range between 500oC and 600oC by pyrolysis method. Obtained charcoal was activated using two types of chemicals, KOH and HNO3, and then was doped with Zn and Ni. Furthermore, obtained carbon was made into nanoparticles using High Energy Milling. The structure and properties of the carbon were tested using PSA, SEM, and XRD; and the conductivity was also tested. The smallest particle size was obtained from ‘buluh’ bamboo charcoal with HNO3 activation and without a doping at 1030 nm. The diffractogram and topography of the bamboo charcoal varied depending on the metal doping added. The highest electrical conductivity (DHL) was obtained from betung charcoal with an activator of KOH and a doping of Zn at 7.02 mS/cm.